Graphene oxide incorporated thin film nanocomposite nanofiltration membrane to enhance permeation and antifouling properties - Chengcai Li; Xiuyin Cai; Tong Xu; Huitao Cheng; Guojin Liu; Hailin Zhu; Yuhai Guo (Desalination and Water Treatment)
Aiming at the problems of low permeation flux and low salt rejection of polyamide (PA) nanofiltration (NF) membrane, this study improved the surface properties and structure of PA layer by adding hydrophilic GO nanosheets. Polyethylimide (PEI), GO and trimethylchloride (TMC) were prepared on the surface of polyether sulfone (PES) substrate by interfacial polymerization. After adding GO, the hydrophilicity and zeta potential of NF membrane were improved. The NF test showed that when the amount of GO was 0.1%, the permeation flux of the membrane was increased from 7.06 to 12.285 L·m−2·h−1 (improve 73.94%), and the rejection of MgSO4 was increased from 90.23% to 95.9%. In the test of repulsion of univalent ion and bivalent ion, the repulsion value of bivalent ion is above 95%, and the repulsion degree of univalent ion is moderate. Compared with the original TFC membrane, the composite membrane also showed higher anti-fouling. This study provides a shortcut for improving the hydrophilicity and anti-fouling properties of NF membranes by using GO nanosheets.